Organized cross-atlantic crime: racketeering in fuels - Duyne, Petrus C. van (Crime, law and social change, 1994)
There is concern about penetration of organized crime in the legitimate business. This penetration can take various forms, ranging from a complete ‘take over’ to a veritable symbiosis between crime-enterprises and the legitimate industry. This paper describes the interaction between crime-enterprises in the mineral oil market in the Unites States and North-western Europe. It pictures the landscape or moral decay, lack of supervision by law enforcement and the spread of systematic fraud in a branch of industry which has become ripe for infiltration by organized crime. The paper reveals that organized business crime is not just a concern for the United States of Europe alone. If the entrepreneurial landscape has similar features and there are possibilities of personal bridgeheads organized business crime obtains crossborder, transatlantic dimensions. The paper questions the selective attention of law enforcement to easily recognizable crime and the morally dubious attitude of legitimate industry taking advantage of the profitable offers by criminal entrepreneurs.